Immunoregulation and clinical significance of neutrophils/NETs-ANGPT2 in tumor microenvironment of gastric cancer - Yang, Shifeng; Zou, Xiaoming; Li, Jiacheng; Yang, Hao; Zhang, Ange; Zhu, Yanli; Zhu, Lei; Zhang, Lisha (Frontiers in Immunology, 2022)
Although significant progress has been made in the study of gastric cancer (GC), clinicians lack reliable protein markers for accurate diagnosis and tumor stratification. Neutrophil extracellular traps (NETs) are networks of extracellular fibers composed of DNA from neutrophils. We have previously reported that abundant NETs are deposited in GC, damaging human umbilical vein endothelial cells (HUVECs) and triggering the release of tissue factors, leading to a hypercoagulable state in GC. However, the specific effects of NETs on HUVECs are unclear. We aimed to explore the functional changes caused by NETs on HUVECs, providing evidence that NETs may fuel GC progression. Through quantitative proteomics, we identified 6182 differentially expressed proteins in NET-stimulated HUVECs by TMT. The reliability of the TMT technique was confirmed by parallel reaction monitoring (PRM) analysis of 17 differentially expressed proteins. Through bioinformatics analysis, we found that NETs upregulate ANGPT2 in HUVECs. We comprehensively analyzed the prognosis, biological function, immune response, and therapeutic value of ANGPT2 in GC. We found that overexpression of ANGPT2 in GC is associated with poor prognosis and potentially regulates multiple biological functions. At the same time, ANGPT2 also predicted immunotherapeutic and chemotherapeutic responses in GC. In conclusion, NETs promoted ANGPT2 overexpression in the GC microenvironment. In the future, the neutrophil/NETs-ANGPT2 axis may provide a new target for the treatment of GC.